Effect of Electroacupuncture ST 36 Zusanli, ST 25 Tianshu, ST 21 Liangmen, CV 12 Zhongwan, and Moxibustion CV 8 Shenque on Cases of Gastric Pain - Wardhani, Resa Kusuma; Prasetya, Hanung; Zulaika, Chusnul; Sumanto (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
Gastric pain is a symptom felt as heartburn caused by inflammation of the gastric mucosa. Electroacupuncture and moxibustion therapy are therapeutic methods that have significant results in reducing gastric pain. This study aimed to determine the effect and difference of electroacupuncture therapy ST 36, ST 25, ST 21, CV 12 with electroacupuncture at points ST 36, ST 25, ST 21, CV 12 and CV 8 moxibustion on cases of gastric pain in Kutoharjo Village. Quasi-experimental research with Nonequivalent Control Group Design. A sample of 30 subjects was divided into 2 groups given electro-acupuncture therapy and electroacupuncture therapy combined with moxibustion. Pain scale was measured using Numeric Rating Scale (NRS) before and after intervention. Data were analyzed using Mann-Whitney and Wilcoxon tests. The results showed a significant decrease in the NRS pain scale after intervention in both groups (p<0.050). The Mann-Whitney test showed a significant difference between the two groups (p = 0.009), with the electroacupuncture group with CV 8 moxibustion showing a more significant reduction in pain than the electroacupuncture group. Wilcoxon test showed a significant reduction in pain scale in both groups (p<0.001). This study shows that electroacupuncture with CV 8 moxibustion is more effective than electroacupuncture in reducing the gastric pain scale. These results show a significant value, which can be taken into consideration to reduce gastric pain.